Mechanism of Surfactant Enhancement of CO2 Displacement Recovery in Interlayer Shale Oil Reservoirs - Lanlan Yao; Qihong Lei; Zhengming Yang; Youan He; Haibo Li; Guoxi Zhao; Zigang Zheng; Haitao Hou; Meng Du (Geofluids)
Aiming at the problem that few studies have been conducted on the combination of multiple media in enhanced oil recovery (EOR), the physical simulation experiment of surfactants + CO2 (SPC) was carried out to analyze the influence of surfactant on the CO2 displacement effect of interlayer shale oil reservoir. The results show that when the displacement flow volume (DFV) reaches 20 PV, the oil displacement efficiency (ODE) of SPC displacement is 0.42~3.00% higher than that of CO2 displacement. The ODE of small pore displacement can be increased by 1.51~3.61%. And the relative displacement content (RDC) ratio of free oil of tight shale oil reservoir can be increased by 7.10~20.54%. When the DFV is 5 PV, the ODE can be improved more significantly. It shows that the efficiency of small pore displacement can be increased by 1.74~2.33%. It also indicates that the ODE can be increased by 7.03% of the ultralow permeability shale oil reservoir. And the RDC ratio of free oil of tight shale oil reservoir can be increased by 10.34~21.50%. Surfactant can improve the wettability of the reservoir and make the rock sample wet. This research can help to understand the influence of surfactant on CO2 displacement effect and reveal the mechanism of SPC displacement improving the ODE of interlayer shale oil reservoir, providing theoretical basis for the effective development of interlayer shale oil reservoir.